Certain polyhydroxylated amines in the genesis of dendritic molecules and as potential inhibitors - Finn, M (2000)
This thesis describes investigations into the synthesis and properties of novel cyclic and acyclic polyhydroxylated amines arising from carbohydrate derivatives or from the union of simpler, achiral molecules by bespoke de novo construction strategies. These compounds were contrived on the premise of being potential inhibitors of sugar processing enzymes. The highly branched and symmetrical polyhydroxylated amines have found utility in the construction of novel dendritic structures. In studies directed towards the production of acyclic equivalents of nitrogen analogues of monosaccharides it was found that a reductive animation of dihydroxyacetone by ammonium salts with sodium cyanoborohydride gave bis(l,3-dihydroxy-isopropyl)amine [BDI] in good yield and high purity. BDI and its diacetonide are hindered nucleophiles but may be further reductively alkylated to form N-alkyl derivatives. BDI is an open chain equivalent of DMDP [2,5-dideoxy-2,5-imino-D-mannitol] but neither BDI nor its N-alkyl derivatives showed inhibition of any glycosidase or transferase assayed. BDI may provide an example of an AB4 dendritic monomer and initial investigation into the chemistry of this novel branching unit and its expedient origins are addressed. The diacetonide of BDI is a hindered nucleophile with masked hydroxyl groups on the periphery. Various symmetrically and non-symmetrically trisubstituted s-triazines have been synthesised embodying bis(l,3-dihydroxy-isopropyl)amine as a dendritic monomer to furnish highly branched structures with an array of peripheral primary hydroxyl groups. Controlled stepwise 2,4,6-trifunctionalisation of cyanuric chloride with a series of amines including the novel BDI branching unit has genertated a series of dendritic molecules. The variable temperature proton NMR experiments of such molecules showed them to exhibit restricted rotation in solution. The syntheses of these rotationally restricted tri-functionalised s-triazines and the observation of the variable temperature NMR experiments are presented. In studies towards a three-directional molecule incorporating BDI and based on a triazine nucleus a number of dendrimer prototypes were constructed from novel AB4 building blocks. The synthesis of a range of eight carbon, nitrogen containing derivatives utilising carbohydrate lactone starting materials is described. Manipulation of the eight carbon lactone derivatives of protected α-D-glucoheptono-l,4-lactone generated by a Wittig homologation produces a range of novel, highly functionalised precursors containing an α,β-unsaturated ester functionality and a free hydroxyl at C-2. An unsuccessful approach that was anticipated to allow access to eight carbon homologues of α- and β-HNJ from such precursors is described. Formation of the piperidine ring was envisaged to result from the intramolecular 1,3-dipolar cycloaddition of the C-2 azide or from the intramolecular conjugate addition of the tethered nitrogen at C-2 to the α,β-unsaturated ester functionality. It is found that displacement of the 2,3,4-all cis 2-O-triflate derived from aforementioned protected α-D-glucoheptono-l,4-lactone derivatives with sodium azide in DMF gives rise to a kinetic C-2 inverted azide, and a thermodynamic azide cis to the side chain, in which the stereochemistry at C-2 is retained. Additionally an inversion of the C-2 alcohol is described, thus allowing complete control of the stereochemistry at C-2 and consequent tailoring of the desired stereochemistry in the piperidine analogues.